PRODUK HALAL SEBAGAI INSTRUMEN PEMBENTUKAN KARAKTER : TINJAUAN USHUL FIQIH - Husni Rofiq; Nadhir Muammar (Lobi, 2026)
This research aims to analyze the concept of halal from the perspective of Ushul Fiqh and its normative, ethical, and spiritual functions in human life. Furthermore, this study examines the mechanism of halal products as an instrument for character building through the integration of ushuliyah values. The research method employed is descriptive qualitative through library research. Primary data are sourced from classical Ushul Fiqh literature, halal regulations, and related fatwas, while secondary data are obtained from supporting books and journal articles. Data analysis was conducted inductively using content analysis. The results indicate that the concept of halal in Ushul Fiqh does not only determine the legal validity of a product but also serves as a means of moral education. The integration of the principles of maqāṣid al-syarī‘ah, al-amr wa al-nahy, and sadd al-dharī‘ah explains that the consumption of halal products directly contributes to spiritual clarity, discipline, and individual responsibility. Socially, the halal industry fosters a culture of trustworthiness (amanah) and integrity, positioning the role of halal as fundamental in shaping the character of both individuals and society.